Online impulse buying of organic food: a moderated (website personality) mediation (social appeal) process. (13th August 2019) - Tariq, Anum; Wang, Changfeng; Tanveer, Yasir; Akram, Umair; Bilal, Muhammad
While existing literature has addressed the antecedents of impulsive buying behaviour, this research study investigates the impulse buying of organic food through mediating effect of social appeal on the relationship between consumer attitude and online impulse buying behaviour and whether this mediated relationship is moderated by website personality. In total, 600 respondents were asked to fill online survey questionnaire, however, 423 valid responses were collected in Beijing, China. Data were collected in a period of three months from October-December 2017 by survey questionnaire placed on frequently used social media platform like Wechat, QQ and Sina Weibo. Results revealed a significant full mediation in a positive relationship. This mediating effect of social appeal is further moderated by website personality. Results instigate online marketing professionals to review their tactics to deal with modern consumers by developing websites with social learning mechanism, user-friendlier and visually appealing to push organic intake.